PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KERJA SAMA DAN HASIL BELAJAR SISWA KELAS IV SDN BHAKTI WINAYA BANDUNG PADA SUBTEMA KEBERSAMAAN DALAM KEBERAGAMAN - Mumin Saud, Abdul; Oktiana, Letty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2016)
The study, titled "Model Problem Based Learning to Enhance Cooperation and Learning Outcomes Student Class IV SDN Bhakti Winaya Bandung on Subtheme Unity in Diversity", against the background because of their problems in the field of the learning outcomes of students who mostly have reached completeness and lack of implementation of activities the cooperation of students during the learning process. This study uses classroom action research model, which consists of the third cycle. Each cycle consists of several actions, planning, implementation, analysis and reflection. The results of the first cycle studies show the learning outcomes of students achieving mastery percentage of 60.7% with an average value of students 2.5, for the same work values of students in this cycle are categorized in category (quite good) with the average value of students 2, 4. While the second cycle which is an improvement from the first cycle of learning outcomes increased by 85.7% with an average value of 2.8 students, and for the value of cooperation on sisklus II is categorized into categories (good) with the average value of students 3. and the third cycle which is a refinement of the second cycle increased learning outcomes by 100% with an average value of 3.7, and for the same work values of students in the third cycle is categorized into categories (good) with the average value of 3 students , 4. Based on the results of this study concluded that the model of problem based learning can improve cooperation and student learning outcomes in grade IV SDN Winaya Bhakti Bandung on subtema unity in diversity. Thus, problem based learning models can be used as an alternative learning models to be implemented on thematic learning.